2010
DOI: 10.1002/jsfa.4079
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of phenolic compounds, amino acids and reducing sugars in commercial potato varieties and their effects on acrylamide formation

Abstract: Careful selection of potato varieties with lower levels of fructose, glucose and asparagine and higher levels of phenolic compounds may mitigate acrylamide formation during thermal processing of potato products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…This is generally attributed to the high content of starch, consecutively leading to a high glycaemic index (GI) [11]. Other components responsible for the detrimental effects of potatoes might be alkaloids or substances synthesized depending on preparation techniques such as acrylamide [12,13]. On the other side, other prospective observational studies have reported either a neutral association [14,15] or an inverse association, providing evidence for beneficial effects of regular potato consumption for the prevention of obesity, CVD, or cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This is generally attributed to the high content of starch, consecutively leading to a high glycaemic index (GI) [11]. Other components responsible for the detrimental effects of potatoes might be alkaloids or substances synthesized depending on preparation techniques such as acrylamide [12,13]. On the other side, other prospective observational studies have reported either a neutral association [14,15] or an inverse association, providing evidence for beneficial effects of regular potato consumption for the prevention of obesity, CVD, or cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…2 A limited studies supposed a negative correlation between acrylamide formation and phenolic (anti-oxidative) composition of its raw natural source (Evers and Deuber 2012). Moreover, Zhu et al (2010) revealed that hydroxycinnamoylquinic/hydroxycinnamoyl derivatives are the major phenolic compounds in potatoes. They also showed that total phenolic content was reversely correlated with aspargine (−0.590) and total sugar quantity (−0.488) in raw potato and acrylamide content (−0.691) in processed form.…”
Section: Role Of Antioxidants In Acrylamide Content Mitigation In Foodsmentioning
confidence: 99%
“…Olea europaea L. 180°C for 5 min (1,000 mg/kg of extract) Urbancic et al, 2013 hemoglobin, and different functional groups of proteins like SH, inducing gene mutation and chromosomal aberration, increasing benign and malignant neoplasm in rodents (Casado et al 2010;Kalita et al 2013;Pelucchi et al 2011;Salazar et al 2012a;Zhu et al 2010).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations